Tag7 (PGLYRP1) Can Induce an Emergence of the CD3+CD4+CD25+CD127+ Cells with Antitumor Activity - T. N. Sharapova; E. A. Romanova; L. P. Sashchenko; D. V. Yashin (Journal of Immunology Research)
We have shown that in the human peripheral blood cells, the innate immunity protein Tag7 can activate a subpopulation of CD3+CD4+CD25+ cells, which have antitumor activity. These cells can induce lysis of HLA-negative tumor cell lines. The Hsp70 stress molecule on the surface of the tumor cells is used as a recognition target, while the Tag7 protein on the lymphocyte membrane acts as a receptor for Hsp70. We have also demonstrated that this subpopulation of the CD4+CD25+ cells is CD127 positive and hence is not the Treg cells. Our data suggest that this subpopulation of cells is identical to the CD4+CD25+ lymphocytes, which are activated in the leukocyte pool by the IL-2 cytokine.